Il prelievo delle cellule staminali mesenchimali dal tessuto adiposo - Battaglini, G.; Guadalascara, F.; Monteleone, G. (Lo Scalpello - Journal, 2019)
MESENCHYMAL CELLS SAMPLING FROM ADIPOSE TISSUE The treatment of chondral and tendinous lesions with staminal cells is today widely used and well accepted by the scientific community. In our first attempts, we did not pay much attention to the phase of sampling mesenchymal cells from the adipose tissue. Local complications and aesthetic gripes led us to a constant evolution in the sampling technique. Today, we have achieved a good sampling technique with a very low rate of local complications and virtually invisible scars.